Modified mesoporous HMS supported Ni for deoxygenation of triolein into hydrocarbon-biofuel production - Zulkepli, Suraya; Juan, Joon Ching; Lee, Hwei Voon; Abd Rahman, Noorsaadah; Show, Pau Loke; Ng, Eng Poh (Elsevier, 2018)
A series of modified hexagonal mesoporous silica (HMS) supported by various Ni loading (5 wt% Ni, 10 wt% Ni, 40 wt% Ni and 100 wt% Ni) have been synthesized and systematically characterized. The resultant Ni catalysts improved the performance of the deoxygenation (DO) of triolein at a reaction temperature of 380 °C in a simple glass batch reactor under a solvent-free condition and are hydrogen-free. The incorporation of Ni loading into the HMS framework casued the catalytic activity to increase when compared to that of HMS. Surprisingly, 10 wt% Ni/HMS catalyst exhibited the highest conversion. It was observed that 10 wt% Ni loading was highly dispersed on the HMS which is capable of achieving 92.5% and 95.2% of conversion and selectivity, respectively. This is due to the synergistic effect of Si-O-Ni bonding and high dispersion of NiO on HMS. In this respect, the nature of catalyst support such as pore size and the high surface areas of HMS play an important role in enhancing the catalytic performance of DO reaction. This study has revealed that Ni/HMS catalyst is a promising catalyst that can be applied to the development of sustainable biofuel from non-edible oil.